The Effect of Human Resource Development on Employee Performance at the Civil Service and Human Resources Development Agency of South Buton Regency - Asmiddin Asmiddin; Syahril Ramadhan; La Ode Hasri (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2021)
This research aims to find out and analyze the influence of human resource development on the performance of the Personnel and Human Resources Development Agency employees of South Buton Regency. This study uses an explanatory quantitative method, namely research that explains the effect of certain variables on other variables. The population of this study were all civil servants of the Agency for Personnel and Human Resources Development of South Buton Regency, totaling 23 people. The sampling technique used a saturated sample, namely the entire population was used as the research sample. Data were collected through questionnaires and observation. The data analysis technique used descriptive and inferential analysis. The results showed that pHuman resource development has a positive and significant effect onThe performance of the BKPSDM South Buton Regency employees, this is shown through the results of the regression significance test, therefore it is suggested that the promotion section of the service is more transparent and adjusts placement, competence, knowledge, skills, experience, education and training, increased discipline, and speed in working to be enthusiastic to work better according to the main tasks and functions of the brand based on the targets that have been set.